Komposisi Makrozoobentos di Sungai Desa Tolomato Kecamatan Suwawa Tengah, Kabupaten Bone Bolango, Provinsi Gorontalo - Febiyanti Padja; Ade Irma Polamolo; Miftahul Khair Kadim; Nuralim Pasisingi (Jurnal Sumberdaya Akuatik Indopasifik, 2021)
Tolomato Stream is a small river located in Tolomato Village which is directly connected to the main river in Gorontalo Province, namely the Bone River. The method used was a survey and purposive sampling. The research objective was to determine the structure of the macrozoobenthic community in the Tolomato stream. The results showed that 1,181 individuals were divided into 11 families. There were 6 orders of macrozoobenthos (Diptera, Ephemeroptera, Coleoptera, Trichoptera, Plecoptera, Lepidoptera) and 11 families (Chironomidae, Ceratopogonidae, Tabanidae, Limoniidae, Athericidae, Baetidae, Caenidae, Elmidae, Hydropsychidae, Perlodidae, Crambidae classes). The composition of macrozoobenthos that was mostly found was from the Diptera order of 80%.